Missteps in Managing the COVID-19 Crisis - McDonnell, Joseph (Maine Policy Review, 2021)
The Covid-19 pandemic surprised the world with the speed of its spread and caught nations woefully unprepared to contain the virus but in hindsight its arrival was readily predictable. Why did the warning signs for Covid-19 go unnoticed? Why did so many leaders fail to plan for a pandemic? And why did they not recognize the outbreak and respond effectively even after the pandemic was at their doorstep? This paper will seek to answer these questions by exploring six stages in crisis management: 1) preventing the crisis, 2) planning for the crisis, 3) recognizing the crisis, 4) containing the crisis, 5) returning the society to normal or non-crisis state, and 6) learning from the crisis. The paper uncovers missteps to aid society to better prepare for the next crisis